PEMANFAATAN PERLIT YANG TELAH DIMODIFIKASI UNTUK AMOBILISASI ENZIM BROMELAIN - Elida Mardiah (Universitas Andalas, 2009)
ABSTRACT Amobilization of bromelaine enzyme extracted from ananas fruit (Ananas comusus) acetone has been done. Modified perlite in the amino silica phosphat (ASP) is used as matrix amobilization. The protein content has determined by Lowry method, while enzyme activity were determined by Anson method caseine as substrate. It native enzyme specific activity was 0.1281 unit/mg with konsentration 20000 ppm, pH 7.0, incubation time 35 minutes, and temperature 40°C. Amobil bromelaine specific activity was 0.7438 units/mg with substrate on 20000 ppm pH 7.0, incubation time 30 minutes and temperature 37°C. This bromelaine enzymes activity was increased six times than native enzim and showed the activity for several repeatation. Keywords: perlit, enzim bromelain, amobilization